RELATIONAL FUNCTIONS OF ADDRESS TERMS IN LITTLE WOMEN - Eva Utami Durahman (Linguistik : Jurnal Bahasa dan Sastra, 2026)
This study examines the use of address terms and their relational functions in the dialogue between characters in Chapter 1 of Louisa May Alcott's novel Little Women using a pragmatic-sociolinguistic approach. Language in literary works not only functions as an aesthetic medium, but also as a medium for representing social relations between characters that are constructed through specific linguistic choices. The research data consists of 43 dialogues between characters that contain explicit and implicit forms of address. The data were analyzed qualitatively by using dialogic utterances as the unit of analysis, rather than isolated sentences, in order to capture the relational meaning in context. The results show that address terms in Little Women appear in various forms, such as kinship terms, personal names, affective forms of address, and forms of address without explicit lexical forms. These forms serve to build and negotiate emotional closeness, solidarity, family hierarchy, and social control between characters. The analysis also shows that relational functions are not static, but dynamic and dependent on the context of interaction and the development of relationships in the narrative plot. These findings confirm that literary dialogue can be treated as a valid social communication practice for linguistic analysis. This research contributes to the development of literary pragmatics by integrating the analysis of address terms and relational functions in the context of classic children's literature, which has been studied more from a thematic and ideological perspective.